Functional characterization of the antiepileptic drug candidate, padsevonil, on GABAA receptors. (16th April 2020) - Niespodziany, Isabelle; Ghisdal, Philippe; Mullier, Brice; Wood, Martyn; Provins, Laurent; Kaminski, Rafal M.; Wolff, Christian
Abstract: Objective: The antiepileptic drug candidate, padsevonil, is the first in a novel class of drugs designed to interact with both presynaptic and postsynaptic therapeutic targets: synaptic vesicle 2 proteins and γ‐aminobutyric acid type A receptors (GABAA Rs), respectively. Functional aspects of padsevonil at the postsynaptic target, GABAA Rs, were characterized in experiments reported here. Methods: The effect of padsevonil on GABA‐mediated Cl − currents was determined by patch clamp on recombinant human GABAA Rs (α1β2γ2) stably expressed in a CHO‐K1 cell line and on native GABAA Rs in cultured rat primary cortical neurons. Padsevonil selectivity for GABAA R subtypes was evaluated using a two‐electrode voltage clamp on recombinant human GABAA Rs (α1‐5/β2/γ2) in Xenopus oocytes. Results: In recombinant GABAA Rs, padsevonil did not evoke Cl − currents in the absence of the agonist GABA. However, when co‐administered with GABA at effective concentration (EC)20, padsevonil potentiated GABA responses by 167% (EC50 138 nmol/L) and demonstrated a relative efficacy of 41% compared with zolpidem, a reference benzodiazepine site agonist. Similarly, padsevonil demonstrated GABA‐potentiating activity at native GABAA Rs (EC50 208 nmol/L) in cultured rat cortical neurons. Padsevonil also potentiated GABA (EC20 ) responses in GABAA Rs expressed in oocytes, with higher potency at α1‐ and α5‐containing receptors (EC50 295 and 281 nmol/L) than at α2‐ and α3‐containing receptors (EC50 1737 and 2089 nmol/L). Compared with chlordiazepoxide—a nonselective, full GABAA R agonist—the relative efficacy of padsevonil was 60% for α1β2γ2, 26% for α2β2γ2, 56% for α3β2γ2, and 41% for α5β2γ2; no activity was observed at benzodiazepine‐insensitive α4β2γ2 receptors. Significance: Results of functional investigations on recombinant and native neuronal GABAA Rs show that padsevonil acts as a positive allosteric modulator of these receptors, with a partial agonist profile at the benzodiazepine site. These properties may confer better tolerability and lower potential for tolerance development compared with classic benzodiazepines currently used in the clinic.